Wyróżnik człowieczeństwa - Szyszkowska, Maria (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2013)
Who is a human being? What is the aspect that marks out its humanity? Are individuals in the right to recognize themselves as better than other creatures? What is the discrimination of intellectually inferior person? The considerations proposed by the author became the basis to reflect on the situati